A case management model for patients with granulomatous mastitis: a prospective study - Yuan Deng; Ying Xiong; Ping Ning; Xin Wang; Xiao-Rong Han; Guo-Fang Tu; Pei-Yu He (BMC, 2022)
Abstract Background Granulomatous mastitis (GM) is a chronic inflammatory mastitis disease that requires long-term treatment and has a high recurrence rate. Case management has been proven to be an effective mechanism in assisting patients with chronic illness to receive regular and targeted disease monitoring and health care service. The aim of this study was to investigate the application of a hospital-to-community model of case management for granulomatous mastitis and explore the related factors associated with its recurrence. Methods This was a prospective study on patients with granulomatous mastitis based on a case management model. Data on demographic, clinical and laboratory information, treatment methods, follow-up time, and recurrence were collected and analyzed. The eight-item Morisky Medication Adherence Scale (MMAS-8) was used to investigate patients' adherence to medications. Logistic regression models were built for analysis of risk factors for the recurrence of granulomatous mastitis. Results By October 2021, a total of 152 female patients with a mean age of 32 years had undergone the entire case management process. The mean total course of case management was 24.54 (range 15-45) months. Almost all the patients received medication treatment, except for one pregnant patient who received observation therapy, and approximately 53.9% of the patients received medication and surgery. The overall recurrence rate was 11.2%, and "high" medication adherence (RR = 0.428, 95% CI 0.224-0.867, P = 0.015) was significantly associated with a lower rate of recurrence, while the rate of recurrence with a surgical procedure + medication was higher than that with medication alone (RR = 4.128, 95% CI 1.026-16.610, P = 0.046). Conclusion A case management model for patients with granulomatous mastitis was applied to effectively monitor changes in the disease and to identify factors associated with disease recurrence. "Low" medication adherence was a significant risk factor for the recurrence of granulomatous mastitis. Patients treated with medication and surgery were more likely to experience recurrence than those treated with medication alone. The optimal treatment approach should be planned for granulomatous mastitis patients, and patient medication adherence should be of concern to medical staff.